Funny Punny Logic. (29th January 2018) - Roberts, Alan
Abstract: Humour has been a surprisingly neglected topic in philosophy. However, Noah Greenstein has recently given an intuitive schema for modelling the logical structure of puns. Having this logical structure is indeed what makes a pun punny, but I argue that it is not what makes a pun funny. In order for a pun to be funny, the components comprising its logical structure must be related to one another such that certain conditions are satisfied. By using Graeme Ritchie's linguistic model of jokes, I give these conditions in terms of those components.